Solving "Einstein's Riddle" Using Spreadsheet Optimization - Yeomans, Julian Scott (Transactions on education, 2003)
A solution to Einstein's Riddle is presented using spreadsheet modelling and optimization. Various versions of this problem have been used in introductory management science (MS) classes either as an assignment or as a take-home exam. This riddle has proved to be a challenging problem, since it simultaneously integrates many of the elements that are taught throughout the semester. Namely, the ability to convert a somewhat complicated verbal description into requisite constraints, the creative modelling skills required to transform the problem into an assignment problem-type structure, no "true" or obvious objective function, a difficulty in determining what the (non-obvious) decision variables should be, the use of integer (binary) variables together with either-or constraints requiring satisfaction at equality (an added technical difficulty/challenge), the ubiquitous time issues involved in the solution of integer problems, the numerical representation of numbers by computers that are not readily obvious to business students (i.e. why supposedly integer values may appear in some form of scientific notation) and, most importantly, the ability to appropriately structure the problem formulation into a spreadsheet format for implementation with Solver.